The inconsistent mediating effect of catechol O methyl transferase Val158Met polymorphism on the sex difference of cognitive impairment in schizophrenia patients - Xu, Hang; Zhou, Yongjie; Xiu, Meihong; Chen, Dachun; Wang, Weiwen; Wang, Li; Zhang, Xiangyang (Frontiers in Psychiatry, 2022)
Objective: Schizophrenia is a multifaceted mental disorder characterized by heterogeneous positive/negative symptoms and cognitive deficits. Sex differences have been reported in various aspects of the disease. However, the underlying genetic reasons remain unelucidated. Recent studies show that the influence of COMT Val158Met (rs4680) variation is sexually dimorphic. Thus, this study aims to explore whether there is an effect of the interaction between COMT Val158Met (rs4680) polymorphism and sex on patients’ clinical characteristics and cognitive function. Methods: We recruited 367 inpatients with chronic schizophrenia (246 males and 121 females) and 419 healthy controls (172 males and 247 females). The cognitive performance was assessed by Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), and the COMT Val158Met (rs4680) polymorphism is genotyped. The psychopathological symptoms of the patients were assessed by the Positive and Negative Syndrome Scale (PANSS). Results: We find that male patients had a significantly higher proportion of carrying the Val allele and Val/Val carriers exhibited more severe positive symptoms and cognitive impairment than Met carriers. COMT Val158Met (rs4680) polymorphism inconsistently mediated the relationship between sex and cognitive performance in schizophrenia patients. Conclusion: These findings suggest that COMT Val158Met (rs4680) polymorphism is associated with the risk and severity of schizophrenia in a sexually dimorphic way and contributes more to the clinical symptoms and cognitive impairment in male patients with schizophrenia.